Putinism : the slow rise of a radical right regime in Russia - Herpen, Marcel H. van 1945- (Palgrave Macmillan, 2013)
"This book aims to provide an important insight into the essence of Putinism and the political system he has established in Russia over the past decade. Van Herpen compares in detail the many and often surprising parallels that exist between Vladimir Putin's regime in Russia and that of Weimar Germany and Mussolini's Italy indicating the presence of strong Fascist elements in the contemporary Russian Political system. However, this is tempered with elements of Bonapartism from Napoleon III's France and the populism of Italian politics under Berlusconi creating a hybrid system which has been termed 'Fascism-Lite' with a softer face than Mussolinian Fascism but still containing a hard core of ultra-nationalism, militarism and neo-imperialism. The author not only looks at Putin's regime in retrospect but also offers an insight into the future of the Russian political system as Russia's strong man begins his third term in office"--